Strategic Profiling and Analytic Modelling of Node Misbehaviour in Adhoc Networks via Game Theory - Olanrewaju, Rashidah Funke; Hassan Abdalla Hashim, Aisha; Yusoff, Siti Hajar (2018)
Ubiquitous Computing and Internet of Things (IOT) are extremely popular in recent age and therefore imparting high level security mechanism is highly indispensable for such advanced technical systems. However, the security problems in Mobile Adhoc Networks (MANETs) are a constant topic of interest and have been drawing attention of research community from the past decade, where massive study has already been witnessed for addressing the security affairs. One of the precarious problems encountered in MANET is that of identifying the malicious nodes. This is because nodes in MANET are equally influential to take accountability during transmission. Coordination among nodes during communication and working without control of any central manager truly ensembles them to be applied in IoT. However, the identification and later mitigation of malicious nodes becomes an immensely difficult task especially when Selfish/Erroneous nodes exist along with normal Collaborative nodes in the Regular camp. The presence of selfish nodes is potentially harmful as similar behaviour can be imitated by malicious nodes which are the point of concern of many security aspects. While reviewing some techniques on the security system in MANET, it was found that game theory had a prime contribution in the past few years due to potential accuracy in its probabilistic approach and computational efficiency. Therefore, this study accentuates the use of game theory and probability theory considering selfish nodes in the regular node camp while modelling the Regular versus Malicious node game and thereby enhancing the prior mathematical schema of strategical decision making to accommodate for the same. The proposed study performs statistical analysis and presents a mathematical model to mimic the multi-stage game between regular and malicious node using Game Theory. Furthermore, it does not use any complex cryptographic protocols that tend to increase network overhead. The framework tries to effectively represent the various unpredictable actions of node cooperation, node declination, node attacks as well as node reporting that can model the strategic profiling of various mobile nodes. Understanding the patterns and then deploying the algorithms in security products can reduce intrusion to a greater extent